ANALISIS MOTIVASI BELAJAR SISWA KELAS V SD INPRES 3/77 ARASOE KECAMATAN CINA KABUPATEN BONE DALAM PEMBELAJARAN IPAS - Sudarto , Sudarto; Aabd. Kadir; Amalia Ramadhani (Jurnal Cakrawala Ilmiah, 2025)
This study is a qualitative study that aims to determine the Student Learning Motivation in IPAS learning. The subjects in this study were of the fifth grade students of SD Inpres 3/77 Arasoe. The data collection techniques for this study were of the interview, observation and questionnaire techniques. The data analysis techniques in this study were of data reduction, data presentation and drawing conclusions. The results and the conclusions of the study showed a picture of the learning motivation of fifth grade students at SD Negeri 3/77 Arasoe in IPAS learning, namely the students ask the teacher if there are some things that are considered difficult to understand without being asked to ask, the students look for references themselves to find out the answers the problems that they do not know the solution to, the students have aspirations to succeed, students remain committed to learning even though they do not get awards, and the students hope that learning IPAs is always in the form of practice